The effect of person job fit, person organization fit, and self efficacy on employee career success in financial institution - Syahirah, Musa (2020)
Career success is one of important factors that employees search for in building their career. This study aims to examine the influence of person-job fit, person-organization fit and self-efficacy on career success among employees in a financial institution in Kuala Lumpur. A total of 308 employees from financial institution participated in the study. Three hypotheses were tested using SPSS 25. The findings indicated that only person-job fit and self-efficacy were significant and positively related to career success. This study also provided theoretical and practical implications in which career success progression can be influenced by several predictors. This study contributes to the body of knowledge, particularly the domain of career success.